ANALISIS PENGUASAAN KONSEP EFEK RUMAH KACA PADA MAHASISWA PENDIDIKAN FISIKA ANGKATAN 2016 UNIVERSITAS JEMBER (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2021)
The greenhouse effect is the process by which radiation from a planet's atmosphere warms a planet's surface to a temperature higher than what it would be if there were no atmosphere. Catherine Gautier (2006) in a class shows that students are often unaware of their misunderstanding of their representations when compared to scientific representations. One of the factors that can influence misconceptions in students is an error in interpreting the meaning conveyed. This study aims to test the mastery of the concept of the greenhouse effect on students. The sample used in this study was 50 students of Physics Education class of 2016 at the University of Jember who were taking their fourth semester. Methods The research is carried out with quantitative methods. The method of collecting data is a questionnaire obtained from open questions (in the form of essays) posed to students of Physics Education class 2016 at the University of Jember, totaling 10 questions. Based on the results of data analysis, it can be concluded that there are students who have misconceptions about the greenhouse effect.Keywords: Atmosphere, Greenhouse Effect, Misconception, Temperature.